Walking Training Enhances Corticospinal Excitability in Progressive Multiple Sclerosis—A Pilot Study - Chaves, Arthur R.; Devasahayam, Augustine J.; Riemenschneider, Morten; Pretty, Ryan W.; Ploughman, Michelle (Frontiers in Neurology, 2020)
Background: Inflammatory lesions and neurodegeneration lead to motor, cognitive and sensory impairments in people with multiple sclerosis (MS). Accumulation of disability is at least partially due to diminished capacity for neuroplasticity within the central nervous system. Aerobic exercise is a potentially important intervention to enhance neuroplasticity since it causes upregulation of neurotrophins and enhances corticospinal excitability which can be probed using single-pulse Transcranial Magnetic Stimulation (TMS). Whether people with progressive MS who have accumulated substantial disability could benefit from walking rehabilitative training to enhance neuroplasticity is not known. Objective: We aimed to determine whether 10 weeks of task-specific walking training would affect corticospinal excitability over time (PRE, POST and 3-month Follow-Up) among people with progressive MS who required walking aids. Results: Eight people with progressive MS (7 females; 29-74 years-old) with an Expanded Disability Status Scale of 6-6.5 underwent harness-supported treadmill walking training in a temperature controlled room at 16°C (10 weeks; 3 times/week; 40 minutes at 40-65% heart rate reserve). After training, there was significantly higher corticospinal excitability in both brain hemispheres; reductions in TMS active motor thresholds and increases in motor evoked potential amplitudes and slope of the recruitment curve (REC). Decreased intracortical inhibition (shorter cortical silent period) after training was noted in the hemisphere corresponding to the stronger hand only. These effects were not sustained at follow-up. There was a significant relationship between increases in corticospinal excitability (REC, area under the curve) in the hemisphere corresponding to the stronger hand and lessening of both intensity and impact of fatigue on activities of daily living (Fatigue Severity Scale, and Modified Fatigue Impact Scale, respectively). Conclusion: Our pilot results support that vigorous treadmill training can potentially improve neuroplastic potential and mitigate symptoms of the disease even among people who have accumulated substantial disability due to MS.